Pengaruh Regulasi Emosi terhadap Self-Injuries Behaviour pada Dewasa Awal di Kota Bandung - Andi Adyzha Sanika Firstania; Eni Nuraeni Nugrahawati (UNISBA Press, 2024)
Abstract. Self-injury is a behavior of harming oneself without any suicidal intent. This often occurs in early adulthood individuals with low emotional regulation due to their difficulty in controlling their emotional responses, making them more prone to emotional outbursts or impulsive behaviors that lead to the use of maladaptive coping strategies, namely self-injury. Therefore, it requires individuals to have the ability to control and regulate their emotions, as well as to know when to express or suppress emotions in certain situations, especially when faced with pressure from the surrounding environment or commonly referred to as emotional regulation. This research is a quantitative study using causal and accidental sampling methods. A total of 150 young adults in the city of Bandung aged 18-25 years old were the subjects of the study. Data analysis was conducted using multiple linear regression, while data collection utilized the Inventory of Statements About Self-Injury (ISAS) and the Emotion Regulation Questionnaire (EQS). The analysis results indicate a negative relationship between emotional regulation and self-injury at 26.9%. This implies that the lower the emotional regulation, the higher the level of self-injury behavior. Abstrak. Self-Injury merupakan perilaku menyakiti diri tanpa ada niatan bunuh diri. Hal ini sering terjadi pada dewasa awal yang memiliki regulasi emosi yang rendah dikarenakan individu cenderung sulit mengontrol respons emosional mereka, sehingga lebih rentan terhadap ledakan emosi atau perilaku impulsive yang menyebabkan individu tersebut menggunakan strategi koping maladaptive yaitu self-injury. Maka dari itu diperlukan kemampuan individu untuk mengendalikan dan mengatur emosi mereka, serta mengetahui kapan harus mengekspresikan atau menahan emosi dalam situasi tertentu, terutama saat dihadapkan pada tekanan dari lingkungan sekitar atau biasa disebut regulasi emosi. Penelitian ini merupakan penelitian kuantitatif yang menggunakan metode kausalitas dan accidental sampling. Sebanyak 150 dewasa awal di Kota Bandung dengan rentang usia 18-25 tahun menjadi subjek penelitian. Analisis data dilakukan menggunakan regresi linear berganda, sementara pengumpulan data memanfaatkan Inventory of Statements About Self-Injury (ISAS) dan Emotion Regulation Questionnaire (EQS). Hasil analisis menunjukkan bahwa terdapat pengaruh negatif antara regulasi emosi dan self-injury sebesar 26.9%. Yang memiliki arti semakin rendah regulasi emosi makan semakin tinggi tingkat self-injuries behaviour.